PERAN DEWAN PENGAWAS KPK DALAM SISTEM KETATANEGARAAN DI INDONESIA - Iqbal Maulana; Mas Anienda Tien Fitriyah (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The birth of several non-structural institutions is a sign that the development of Indonesia's state system is a responsibility to existing problems. The Corruption Eradication Commission is one of the institutions that was founded in 2003. This was born because the culture of corruption has spread to state administrators, including the police and prosecutors. The Corruption Eradication Commission has independent characteristics in carrying out its duties, namely it must avoid power intervention by both legislative, executive and judicial powers. Because in essence, the three components of the branch of power are the main components in the administration of the State which are also objects of the supervision of the Corruption Eradication Commission in determining state losses. However, the performance of the Corruption Eradication Commission has not escaped the public scrutiny because it is often considered to be an abuse of power. Law Number 19 of 2019 concerning the second amendment to Law Number 30 of 2002 concerning the Corruption Eradication Commission has created the KPK Supervisory Board which is alleged to be able to carry out the function of checks and balances. This is certainly a new history of the enforcement of corruption laws,, in which the Council has an equal position with the KPK leadership. And the authority given to the Corruption Supervisory Board is also quite central.  This study is a normative juridical research using the statutory approach